Penggunaan Bahan Ajar sebagai Upaya Meningkatkan Kemampuan Literasi Sains Siswa Sekolah Dasar - Toharudin, Uus; Rustaman, Nuryani Y (LP2M IAIN Palangka Raya, 2010)
AbstractThis quasi-experimental research was conducted at three primary schools in the urban area of Bandung in order to reveal the extent to which the role of teaching materials prepared by teachers in developing science literacy skills of primary school students, particularly fifth graders. The learning process uses teaching methods and models that support student mastery of science literacy by developing students hands-on and minds-on skills. Based on the research, there has been difference of mean test scores in science literacy ability of the fifth grade of primary school students significantly before and after the use of science literacy-oriented teaching materials. The results of this study have implications for the implementation of science learning in elementary school so that teachers should develop and use instructional materials that are oriented toward science literacy.Â